Utilización de pellets autorreductores en la producción de aleaciones (hierro-cromo alto carbono) - Pillihuaman Zambrano, Adolfo (2012)
The self-reducing agglomerates were effective in reducing chromites for producing high carbon iron-chromium , improving the speed is reduced , or by increasing the efficiency of chrome recovery and electric power is economizing . The self-reducing pellets of Brazilian chromite containing petroleum coke and 2% Fe -75 % Si, bonded with Portland cement with and without addition of fluxantes (SiO2 and CaO) , were tested at 1773K until there was , evolution of gas reduction . The resulting product was analyzed by electron microscopy and the composition of the phases present by EDS . This work demonstrates that the addition of the composition fluxantes the self-reducing chromite pellets before being reduced causes formation of a slag phase , hindering reduction speed . The results showed that in the self-reducing agglomerates without adding fluxantes , the reduction rate was 2 times faster compared with fluxantes containing at 1773K . This confirms the importance of the mechanism of gas - solid reaction in the carbothermal reduction of the chromite .